2022
DOI: 10.1585/pfr.17.2402032
|View full text |Cite
|
Sign up to set email alerts
|

Fast Signal Modeling for Thomson Scattering Diagnostics and Effects on Electron Temperature Evaluation

Abstract: As a signal processing method for fast digitizers of the switched-capacitor-type in Thomson scattering diagnostics, a "model fitting" method is proposed. An ideal shape of the signal is estimated by this method by averaging many Thomson scattering signals. After applying this method to a relatively low density LHD plasma, the scattering of electron temperature profiles becomes small. The magnitude of error is also reduced by about 60% at some spatial channels in the core plasma. Simulations of signals with som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…By analogy with an electromagnetic oscillator or with an electromagnetic standing wave, where the energy of the electric and magnetic fields are equal, the right-hand sides of equations (7,8) are equated, and the equation (3) of the classical electron radius is obtained from the resulting equality. The bar frequency is determined by the equation:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By analogy with an electromagnetic oscillator or with an electromagnetic standing wave, where the energy of the electric and magnetic fields are equal, the right-hand sides of equations (7,8) are equated, and the equation (3) of the classical electron radius is obtained from the resulting equality. The bar frequency is determined by the equation:…”
Section: Resultsmentioning
confidence: 99%
“…In the horizon of scientific research on the problems of simulation of electrons and electron-related processes, it is worth noting the studies by C. Lamy (on the possibility of using artificial neural networks for modelling non-local electron transport in plasma) [1], B. Tang (on numerical modelling of the processes of suprathermal electron transport in the solar wind) [2], X. An (on modelling the effects of bound electrons in the process of model studies of particles in a cell) [3], Y. Liu (on toroid modelling of electron loss processes flowing out of a 3D field in the organisation of research in the international experimental thermonuclear reactor (ITER)) [4], X. Li (on modelling the processes of acceleration and electron transfer in the early pulsed phase of a solar flare) [5], "Modelling of non-local electron transport in laser-driven double-ablation fronts" [6], "Relaxation of electron beams/strahls in solar outflows: observations vs. modelling" (on the correlated analysis of the results of modelling and full-scale measurements of electron beam/strahl relaxation processes in solar flows) [7], H. Funaba (on the study of the Thomson scattering effect in modelling and estimating electron temperature) [8], D. Vatansever et al (on modelling surfaces that emit electrons when boundary layers are immersed in plasma) [9], V. Lazurik (on the investigation of semi-empirical models of electron beam control in radiation technologies) [10], O. Linder (on self-matching modelling of electron run-up during breakdowns in Tokamak (ITER)) [11], L. Adhikari (on modelling the process of heating protons and electrons in a fast solar wind) [12], M. Wibowo (on modelling the dynamics of ultra-fast electrons in strong magnetic fields using real-time electronic structure methods) [13], Y. Huang (on modelling strong electron heating by radio frequency waves at EAST) [14], Z. Wang (on real-time modelling and estimation of the total electron content in the vertical global ionosphere using hourly IGS data) [15]. When analysing these specialised publications, it was found that in modern physics, electron models only describe its properties.…”
Section: Introductionmentioning
confidence: 99%
“…The electron temperature and density were determined by the commonly used least 𝜒 2 method [6]. Figure 6 compares the results of the error in calculating the temperature from the digitizer signals.…”
Section: System Capabilitiesmentioning
confidence: 99%
“…However, over the last decade, the advent of switched capacitor array (SCA) readout systems [5] has made it possible to measure a large number of channels at GHz sampling rates at low costs. Since direct use of the TS pulse waveform is enhances robustness against noise, fast-sampling analog-to-digital converters (ADCs) are used to measure TS light waveform itself instead of conventional charge-integral digitizers in LHD [6], KSTAR [7], HL-2A [8].…”
Section: Introductionmentioning
confidence: 99%
“…The temporal integration of the signals is needed in the case of the fast digitizers, since the number of photons in the Thomson scattered light is related with the integrated value. The integration is made by a simple summation or by fitting it with some modeled signal shapes [11]. In this paper, integration by simple summation only is used, since fitting for signals of a small S/N ratio is difficult.…”
Section: Lhd Thomson Scattering System and Signal Accumulationmentioning
confidence: 99%